Fast-track pathway for giant cell arteritis: Improved visual outcomes and reduced healthcare costs - Loïc Duron; Thibaud Chazal; Thomas Sene; Julien Savatovsky; Augustin Lecler (PLoS ONE, 2025)
Background Giant cell arteritis (GCA) is the leading vasculitis threatening vision in adults aged ≥ 50 years; permanent vision loss may occur within the first few days after symptom onset. We assessed the impact of a fast-track pathway (FTP) for early diagnosis and treatment of giant cell arteritis in terms of hospitalization patterns and cost-effectiveness. Methods We conducted a retrospective, single-center medico-economic study of consecutive patients referred to a neuro-ophthalmology tertiary center between Nov 1, 2016, and Dec 31, 2022. GCA was defined by ≥ 3 American College of Rheumatology criteria plus a positive temporal-artery biopsy or vascular imaging. An FTP—24/7 access to internal medicine specialists, priority magnetic-resonance imaging, and protocol-driven corticosteroid initiation—was launched on Nov 1, 2018. Demographic, clinical, biological, care-pathway, and cost data were compared before (pre-FTP) and after (post-FTP) implementation. Continuous variables were analyzed with two-sample t tests or Wilcoxon rank–sum tests; categorical variables with χ² or Fisher’s exact test. Findings We included 135 patients (mean age 76 ± 8 years, 61% women): 23 pre-FTP and 112 post-FTP. Baseline characteristics were similar between groups. Compared with the pre-FTP period, the FTP reduced full hospitalizations (62% [69/112] vs 96% [22/23]; p < 0.01) and increased day-hospital or outpatient management (39% vs 4%; p < 0.01). More patients received treatment within one month of symptom onset (54% vs 22%; p < 0.01). Final visual acuity improved (median 2.0 vs 2.6 logMAR; p < 0.01), while cumulative intravenous corticosteroid exposure was significantly reduced (1679 ± 760 mg vs 2295 ± 1055 mg; p = 0.02). Reliance on temporal-artery biopsy fell (17% vs 91%; p < 0.01), owing to a four-fold rise in diagnostic MRI use. Mean total medical costs decreased by €814 per patient (€3672 ± 2861 vs €4486 ± 3193), although this difference did not reach statistical significance (p = 0.23). Interpretation A dedicated fast-track pathway for suspected GCA enables prompt, largely ambulatory care, halves unnecessary full hospitalizations, speeds treatment initiation, improves visual prognosis, and lowers overall expenditure. These findings support wider adoption of imaging-driven FTPs to mitigate the growing clinical and economic burden of GCA.